2016
DOI: 10.3389/fpsyt.2016.00014
|View full text |Cite
|
Sign up to set email alerts
|

Desensitizing Addiction: Using Eye Movements to Reduce the Intensity of Substance-Related Mental Imagery and Craving

Abstract: Eye movement desensitization and reprocessing (EMDR) is an effective treatment for posttraumatic stress disorder. During this treatment, patients recall traumatic memories while making horizontal eye movements (EM). Studies have shown that EM not only desensitize negative memories but also positive memories and imagined events. Substance use behavior and craving are maintained by maladaptive memory associations and visual imagery. Preliminary findings have indicated that these mental images can be desensitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 74 publications
1
24
0
3
Order By: Relevance
“…EMDR has now become an empirically validated and recommended first-line treatment for posttraumatic stress disorders (PTSD) and other conditions that are specifically related to (emotional) stress [e.g., Ref. (23–26)]. The EMDR intervention, as an established procedure for exposing emotional response from trauma therapy, can be used specifically to process emotional distress in patients suffering from chronic pain with the clear objective of processing this dysfunctional emotional shift.…”
Section: Introductionmentioning
confidence: 99%
“…EMDR has now become an empirically validated and recommended first-line treatment for posttraumatic stress disorders (PTSD) and other conditions that are specifically related to (emotional) stress [e.g., Ref. (23–26)]. The EMDR intervention, as an established procedure for exposing emotional response from trauma therapy, can be used specifically to process emotional distress in patients suffering from chronic pain with the clear objective of processing this dysfunctional emotional shift.…”
Section: Introductionmentioning
confidence: 99%
“…Using this laboratory design, different variables can be manipulated in order to examine the underlying working mechanisms of EMDR. Studies that have adopted the model have shown, for example, that memories are not only degraded by EM, but also by other WM taxing dual tasks, such as complex counting (van den Hout et al, 2010) and mindful breathing (van den Hout et al, 2011), and that not only negative memories can be altered by EM, but also positive memories (Engelhard et al, 2010; Hornsveld et al, 2011; Littel, van den Hout, & Engelhard, 2016), providing evidence for the abovementioned WM account.…”
mentioning
confidence: 99%
“…Dementsprechend wurden 37 Treffer aufgrund des Publikationstyps (Buchkapitel oder Dissertation) verworfen, 33 Artikeln wurden aufgrund eines mehrfachen Treffers (unterschiedliche Wortkombinationen, in beiden Datenbanken gefunden) ausgeschlossen und 37 Artikel wurden aufgrund weiterer der eingangs beschriebenen Ein-und Ausschlusskriterien nicht weiter berücksichtigt. Es wurden vier Artikel eingeschlossen [33][34][35][36], welche insgesamt 122 Probanden untersuchten; bei je 30 Probanden lag eine Alkohol-bzw. Zwischen den Gruppen zeigte sich ebenfalls in der TAU + EMDR Gruppe eine signifikante Verbesserung der PTSD-Symptomatik (T = 9,60, p < 0,05).…”
Section: Ergebnisseunclassified
“…Bei Littel et al [34] wurden Probanden Bilder gezeigt, welche zum Rauchen animieren sollten. Nach dieser Craving-Induktion zeigte sich bei Probanden die eine EMDR-Behandlung absolvierten, eine niedrigere Emotionalität hinsichtlich der negativen Erinnerungen.…”
Section: Ergebnisseunclassified
See 1 more Smart Citation